Nicotinic Acetylcholine Receptor Agonists: A Milestone for Modern Crop Protection1. Issue 36 (9th August 2013) - Jeschke, Peter; Nauen, Ralf; Beck, Michael Edmund
Abstract The destruction of crops by invertebrate pests is a major threat against a background of a continuously rising demand in food supply for a growing world population. Therefore, efficient crop protection measures in a vast range of agricultural settings are of utmost importance to guarantee sustainable yields. The discovery of synthetic agonists selectively addressing the nicotinic acetylcholine receptors (nAChRs), located in the central nervous system of insects, for use as insecticides was a major milestone in applied crop protection research. These compounds, as a result of their high target specificity and versatility in application methods, opened a new innovative era in the control of some of the world′s most devastating insect pests. These insecticides also contributed massively to extending our knowledge of the biochemistry of insect nicotinic acetylcholine receptors. The global economic success of synthetic nAChR agonists as insecticides renders the nicotinic acetylcholine receptor still one of the most attractive target sites for exploration in insecticide discovery.